SOSIALISASI DAN PEMBERIAN PUDING DAUN KELOR (PULOR) SEBAGAI UPAYA PENCEGAHAN STUNTING ANAK PRA SEKOLAH - Kartika Mariyona; Pagdya Haninda Nusatri Rusdi; Mega Ade Nugrahmi (MONSU'ANI TANO Jurnal Pengabdian Masyarakat, 2023)
The preschool period is a period that is vulnerable to experiencing malnutrition problems. To fulfill nutritional needs, you can use local food ingredients which are alternatives that can be developed to produce more innovative food variations. This socialization was carried out at Aisyiyah II Kindergarten, Bukittinggi City. By providing outreach and providing Moringa Pudding, the aim is to provide information to teachers about Moringa leaves which can be used as an innovative food ingredient as an effort to prevent stunting in preschool children. Outreach activities can provide new references for teachers regarding processing methods and the benefits of local food ingredients that are abundant in our environment. Respondents enjoyed the Moringa leaf pudding and on average said it was very tasty and liked it. Moringa leaves, which are abundant in abundance, can be used to make various innovative processed ingredients in an effort to prevent stunting in preschool children. Through socialization, it appears that there is additional new knowledge regarding the fairly high nutritional content of Moringa leaves. The teacher appreciated this activity because it provided new understanding and added references about local food processing.